Human perception and responses to flood hazard: A case study from Jhelum district - Nawaz, Falak (Journal of Himalayan Earth Sciences, 2002)
This study attempts to find out the human perceptions and their responses about the flood hazard in district Jhelum, District Jhelum is one of the severely flood-affected areas in Pakistan, worstly affected during the floods of 1992, 1995 and 1997. The study found that the government machinery was mostly engaged in post disaster activities. Concentrating more on the evacuation and rehabilitation measures instead of long-term sustainable solutions. Due to negligence by the implementing agencies, the people are becoming more susceptible to flood hazard. Keeping in view the importance of the problem, an intensive study has been carried out, to find out the human perceptions and responses towards flood hazard; A standard questionnaire was designed, and a survey was conducted in nine selected villages.